The idea of ‘flipped curricula’ and letting students design their own classes: Learning from United Kingdom and Indonesian forest schools - Suharto, Toto; Syaifuddin, Muhammad Irfan; Lawton, Megan J. (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2025)
The present study explores the dynamic interplay between compulsory and self-directed curricula within the unique context of “open schools,” with a particular focus on comparative cases from England and Indonesia. It aims to investigate how these schools, often referred to as jungle or nature schools, navigate the challenges of national curriculum mandates while promoting educational autonomy, inclusivity, and student-centered learning. Employing a qualitative comparative case study design, the research draws on data collected through semi-structured interviews with principals, teachers, and parents, direct classroom observations, and document analysis across six selected schools (three in each country). The findings reveal that these schools employ flexible, innovative curriculum strategies, ranging from full autonomy to hybrid compliance, while integrating nature-based and experiential learning, community governance, and culturally responsive practices. Their responses to national curriculum frameworks vary from strategic adaptation to implicit negotiation or radical autonomy. The study concludes that open schools can offer transformative models of inclusive and holistic education that prioritize developmental needs over uniform standards. Theoretically, the study contributes to debates on curriculum autonomy and inclusive education; practically, it offers insights for educators and policymakers seeking alternatives to one-size-fits-all curricula. While the study is limited to a small sample and qualitative scope, it opens avenues for further research into replicating adaptive curriculum models in diverse global contexts.